Modeling and multi-objective optimization of powder mixed electric discharge machining process of aluminum/alumina metal matrix composite - Talla, G. (Elsevier B.V., 2015)
Low material removal rate (MRR) and high surface roughness values hinder large-scale application of electro discharge machining (EDM) in the fields like automobile, aerospace and medical industry. In recent years, however, EDM has gained more significance in these industries as the usage of difficult-to-machine materials including metal matrix composites (MMCs) increased. In the present work, an attempt has been made to fabricate and machine aluminum/alumina MMC using EDM by adding aluminum powder in kerosene dielectric. Results showed an increase in MRR and decrease in surface roughness (Ra) compared to those for conventional EDM. Semi empirical models for MRR and Ra based on machining parameters and important thermo physical properties were established using a hybrid approach of dimensional and regression analysis. A multi response optimization was also performed using principal component analysis-based grey technique (Grey-PCA) to determine optimum settings of process parameters for maximum MRR and minimum Ra within the experimental range. The recommended setting of process parameters for the proposed process has been found to be powder concentration (Cp)Â =Â 4Â g/l, peak current (Ip)Â =Â 3Â A, pulse on time (Ton)Â =Â 150Â Î¼s and duty cycle (Tau)Â =Â 85. Â© 2015 Karabuk University